2013
DOI: 10.1007/s10973-013-3279-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ferroelastic domain formation on thermal conductivity in Li2TiGeO5 ceramics

Abstract: We show, through thermal conductivity coefficient measurements of Li 2 TiGeO 5 ceramics, that the anomaly associated with the ferroelastic phase transition can be distinguished. We correlate this anomaly with the measurement of the domain structure observed in the vicinity of phase transition temperature T c . Near the T c , the appearance of ferroelastic domains which become new scattering centers for thermal waves, strongly affect the thermal conductivity in Li 2 TiGeO 5 ceramics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…[45][46][47] It has been demonstrated that inorganic ferroelastic materials can be utilized for thermal management applications. 44,[48][49][50] Sieradzki et al studied the changes in the thermal conductivity of Li 2 -TiGeO 5 ceramics in the ferroelastic phase transition or domain formation. 50 Wang et al reported the difference in thermal conductivity values of layered PdSe 2 before and aer ferroelastic phase transition by uniaxial compression and demonstrated that the high ratio of the switchable thermal conductivity value between the two phases could be utilized for exibility and thermal management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[45][46][47] It has been demonstrated that inorganic ferroelastic materials can be utilized for thermal management applications. 44,[48][49][50] Sieradzki et al studied the changes in the thermal conductivity of Li 2 -TiGeO 5 ceramics in the ferroelastic phase transition or domain formation. 50 Wang et al reported the difference in thermal conductivity values of layered PdSe 2 before and aer ferroelastic phase transition by uniaxial compression and demonstrated that the high ratio of the switchable thermal conductivity value between the two phases could be utilized for exibility and thermal management.…”
Section: Introductionmentioning
confidence: 99%
“…44,[48][49][50] Sieradzki et al studied the changes in the thermal conductivity of Li 2 -TiGeO 5 ceramics in the ferroelastic phase transition or domain formation. 50 Wang et al reported the difference in thermal conductivity values of layered PdSe 2 before and aer ferroelastic phase transition by uniaxial compression and demonstrated that the high ratio of the switchable thermal conductivity value between the two phases could be utilized for exibility and thermal management. 44 However, there is only one study concerning the measurement of anisotropic heat transport properties in a superelastic organic crystal due to the limited approaches/techniques to measure the thermal diffusivity of organic crystals.…”
Section: Introductionmentioning
confidence: 99%